2014
DOI: 10.1016/j.neuroimage.2014.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala habituation: A reliable fMRI phenotype

Abstract: Amygdala function is of high interest for cognitive, social and psychiatric neuroscience, emphasizing the need for reliable assessments in humans. Previous work has indicated unsatisfactorily low within-subject reliability of amygdala activation fMRI measures. Based on basic science evidence for strong habituation of amygdala response to repeated stimuli, we investigated whether a quantification of habituation provides additional information beyond the usual estimate of the overall mean activity. We assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 44 publications
(58 reference statements)
7
128
1
Order By: Relevance
“…Based on these prior single-site studies [Johnstone et al, 2005; Lipp et al, 2014; Plichta et al, 2012; Sauder et al, 2013; Van den Bulk et al, 2013], the reliability coefficients for amygdala activation in this study fall within the expected range. Activation was more stable in the right amygdala than the left amygdala, consistent with prior work using the same task (Manuck et al, 2007; Plichta et al, 2014), which may be due to high visuospatial demands of emotion matching rather than underlying neural properties. It has also been suggested that amygdala activation is more reliable to fearful faces than other facial expressions (Sauder et al, 2013; Stark et al, 2004); however, the current block design precluded comparisons by emotional expression.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Based on these prior single-site studies [Johnstone et al, 2005; Lipp et al, 2014; Plichta et al, 2012; Sauder et al, 2013; Van den Bulk et al, 2013], the reliability coefficients for amygdala activation in this study fall within the expected range. Activation was more stable in the right amygdala than the left amygdala, consistent with prior work using the same task (Manuck et al, 2007; Plichta et al, 2014), which may be due to high visuospatial demands of emotion matching rather than underlying neural properties. It has also been suggested that amygdala activation is more reliable to fearful faces than other facial expressions (Sauder et al, 2013; Stark et al, 2004); however, the current block design precluded comparisons by emotional expression.…”
Section: Discussionsupporting
confidence: 84%
“…Emotion labeling and emotion matching were also compared with implicit baseline (consisting of unmodeled fixation events during the intertrial intervals). We selected these contrasts based on prior work with this task [Fakra et al, 2008; Hariri et al, 2000; Lieberman et al, 2007; Plichta et al, 2014]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other potential sources of these inconsistent findings have been suggested, including differences in habituation to emotional stimuli, which have been noted in individuals with BPD [125,126]. Differences in amygdala habituation to fearful stimuli may be a more reliable neural marker than amygdala activation, which may be more variable across an entire task [127,128]. van Zutphen additionally argues that differences in levels of dissociation in individuals with BPD, which is often not assessed in fMRI studies using emotion processing tasks, may account for differences in amygdala activation -that is, dissociation may disrupt emotion processing and amygdala activation [129].…”
Section: Using Functional Neuroimaging To Refine the Diagnostic Constmentioning
confidence: 99%